CHANGES AND TRENDS OF CORN PRODUCTION IN ROMANIA - Elena SOARE; Iuliana DOBRE (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The aim of this paper is to emphasis the main trends on the Romanian corn market. Corn market has a particular importance because of its contribution to feed people and livestock, on the one hand, and, on the other hand, ensure the income for the farmers from export. Using quantitative statistical methods, the paper proposes an economic analysis of corn market in the period 2010-2014. This analysis shows that Romania cultivates large areas with corn, ranking on the first place among European Union countries. Also, in Romania the corn has the highest average production comparatively with the other cereals. The corn remains a key element in Romanian agriculture structure, given that is more increasingly required for export in order to produce biofuels.